Evaluasi dan Efektivitas Program Baznas dalam Pemberdayaan UMKM di Era Covid-19 (Studi Kasus Baznas di Provinsi Jambi) - Yunie Rahayu; Ahmad Soleh; Prima Audia Daniel (J-MAS (Jurnal Manajemen dan Sains), 2022)
The condition of the Covid-19 pandemic without exception all sectors in the economy are affected. More than 70 percent of MSME actors are threatened with going out of business and even dying. Seeing these conditions, Baznas also took part in handling the impact of Covid-19 in the field of economic empowerment. However, the implementation is often still not on target, both in the provision of assistance, the implementation process and its assistance The focus of this research is to discuss the picture of work programs, the level of effectiveness and policy strategies that are carried out by Baznas in Jambi Province. This study used qualitative and quantative desriptif methods using primary data and secondary data. Determination of samples for primary data is carried out by purposive approach and snowball sampling. The scope of this research was carried out on Baznas and MSMEs domiciled in Jambi Province with the research object of Baznas institutions and MSME entrepreneurs who became the object of distributing empowerment program assistance so that two problems were mapped related to each other. The analytical tools used in this study are: to find out the picture of the Baznas program used a deskritif approach, then to see the level of effectiveness of the Baznas program in the empowerment of MSMEs used zakat core principles (ZCP) model and to create policy strategies in the empowerment of MSMEs used SWOT analysis model.